Common Considerations for Genotoxicity Assessment of Nanomaterials - Elespuru, Rosalie K.; Doak, Shareen H.; Collins, Andrew R.; Dusinska, Maria; Pfuhler, Stefan; Manjanatha, Mugimane; Cardoso, Renato; Chen, Connie L. (Frontiers in Toxicology, 2022)
Many standard tests for genotoxicity need methods alterations or specific considerations for valid assessment of nanomaterials (NM).  There are also general considerations, including NM characterization, sample preparation, dosing choice, and data assessment that are applicable to any NM genotoxicity assessment. These are addressed in this paper.  Genotoxicity assessment is a general surrogate for risk related to cancer and heritable genetic alterations.  Thus, genotoxicity testing is performed to determine potential hazard of a chemical or agent. Mechanisms of genotoxicity can be direct, where a substance interacts directly with DNA (or disturbs the mitotic apparatus) to produce DNA lesions, DNA strand breaks, or chromosomal damage leading to definable endpoints such as mutations, chromosomal aberrations, or micronuclei.  Genotoxicity may be indirect, in which case a substance does not interact directly with DNA, but generates DNA mediated biological effects via other mechanisms, e.g., reactive oxygen/nitrogen species (ROS/RNS) or interference with DNA repair.  Because no single assay is capable of detecting all genotoxins or genotoxic mechanisms, a battery of tests is performed to detect both small scale (e.g., point mutations) and large scale (e.g., chromosomal alterations) genetic damage.   The recommendations for NM assessment provided in this Common Considerations document can be used generally with any genotoxicity assay.